2015
DOI: 10.1002/lt.24180
|View full text |Cite
|
Sign up to set email alerts
|

Biliary complications in pediatric liver transplantation: Incidence and management over a decade

Abstract: This study analyzed how features of a liver graft and the technique of biliary reconstruction interact to affect biliary complications in pediatric liver transplantation. A retrospective analysis was performed of data collected from 2001 to 2011 in a single high-volume North American pediatric transplant center. The study cohort comprised 173 pediatric recipients, 75 living donor (LD) and 98 deceased donor (DD) recipients. The median follow-up was 70 months. Twenty-nine (16.7%) patients suffered a biliary comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 50 publications
5
56
1
Order By: Relevance
“…The overall rate of biliary complications in this cohort (23%) is similar to what is reported in the literature . The biliary complication rates according to RTBS use in adults with liver transplants has been studied with RCTs, and conflicting outcomes have been reported.…”
Section: Discussionsupporting
confidence: 78%
“…The overall rate of biliary complications in this cohort (23%) is similar to what is reported in the literature . The biliary complication rates according to RTBS use in adults with liver transplants has been studied with RCTs, and conflicting outcomes have been reported.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, we could not confirm an increased susceptibility for thrombotic events in our PA patients. In addition, the biliary complication rate in our cohort was 14.3%, which is comparable to a rate of 16.7% in children transplanted for other indications . The overall retransplantation rate in children is reported as 13.3%, and in our cohort, it was 14.3% .…”
Section: Discussionsupporting
confidence: 70%
“…In addition, the biliary complication rate in our cohort was 14.3%, which is comparable to a rate of 16.7% in children transplanted for other indications. (32) The overall retransplantation rate in children is reported as 13.3%, and in our cohort, it was 14.3%. (33) Therefore, we have not shown a particular increase in posttransplant complications in our cohort when compared with LT for other indications.…”
Section: Discussionmentioning
confidence: 44%
“…Initially, reported overall graft and patient survival in LDLT compared to DDLT were similar, but more recently, data have suggested that LDLT results in superior outcomes in both adult and pediatric patients. [5][6][7][8][9][10][11] Indeed, in many centers in Asia, Europe, and Canada, the majority of pediatric LT recipients undergo LDLT. 4,[12][13][14][15] The factors which result in superior outcomes with LDLT versus DDLT have not been well characterized.…”
Section: Improved Outcome S In Ldltmentioning
confidence: 99%